2022
DOI: 10.1111/jocn.16265
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mindfulness‐based interventions on psychological well‐being, burnout and post‐traumatic stress disorder among nurses: A systematic review and meta‐analysis

Abstract: Aims and objectives The aim of this study was to investigate the effectiveness of mindfulness‐based interventions on psychological well‐being, burnout and post‐traumatic stress disorder symptoms among working registered nurses. Background Nurses account for nearly half of the global healthcare workforce and are considered significant contributors in multi‐disciplinary healthcare teams. Yet, nurses face high levels of psychological distress, leading to burnout and post‐traumatic stress disorder. Mindfulness‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…In the meta-analysis of burnout, moderate effects were found that are consistent with previous meta-analyses in other populations (Ramachandran et al, 2022;Suleiman-Martos et al, 2020). Both of these meta-analyses mention that mindfulness interventions are only effective in reducing one of the three dimensions of burnout, namely emotional exhaustion (Maslach & Jackson, 1981).…”
Section: Discussionsupporting
confidence: 84%
“…In the meta-analysis of burnout, moderate effects were found that are consistent with previous meta-analyses in other populations (Ramachandran et al, 2022;Suleiman-Martos et al, 2020). Both of these meta-analyses mention that mindfulness interventions are only effective in reducing one of the three dimensions of burnout, namely emotional exhaustion (Maslach & Jackson, 1981).…”
Section: Discussionsupporting
confidence: 84%
“…Twelve randomised controlled trials from 2017 to 2021 were included (Hofmann et al, 2010 ; Hofmann & Gómez, 2017 ; Kabat‐Zinn, 1982 ; Kang & Myung, 2022 ; Liberati et al, 2009 ; Lihua et al, 2017 ; Maharaj et al, 2018 ; Qiu, 2019 ; Rakel, 1999 ; Ramachandran et al, 2022 ; Shapiro et al, 2006 ; Teasdale et al, 2000 ), which involved 807 subjects (405 and 402 in the intervention and control groups, respectively). One study was from Canada (Hofmann et al, 2010 ), one from Japan (Kabat‐Zinn, 1982 ), and the remaining 10 were from China (Hofmann & Gómez, 2017 ; Kang & Myung, 2022 ; Liberati et al, 2009 ; Lihua et al, 2017 ; Maharaj et al, 2018 ; Qiu, 2019 ; Rakel, 1999 ; Ramachandran et al, 2022 ; Shapiro et al, 2006 ; Teasdale et al, 2000 ). Of these, three(Hofmann et al, 2010 ; Hofmann & Gómez, 2017 ; Kabat‐Zinn, 1982 ) were published in English and the remaining nine in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Seven evaluation scales were used to measure the anxiety or depression levels of nurses in the included studies. Since the SCL‐90 (Qiu, 2019 ), HADS (Kabat‐Zinn, 1982 ), DASS (Shapiro et al, 2006 ), HAM‐A (Ramachandran et al, 2022 ), and PAMS‐TA (Hofmann et al, 2010 ) scales were used in only one study, they were not sufficient for the meta‐analysis. A meta‐subgroup analysis of studies that used the SAS and SDS showed that the level of anxiety decreased more with the SAS, and depression decreased more with the SDS.…”
Section: Discussionmentioning
confidence: 99%
“…West et al conducted a systematic review of the evidence for the management of burnout and found strong evidence base for the use of mindfulness, stress management programmes and small group (including reflective) discussions [ 35 ]. Mindfulness has previously been reported as beneficial, although the evidence for it has been reported as moderate to high on systematic review [ 36 ]. There was limited evidence for organisational interventions, mainly due to a lack of studies: it is much more challenging to perform a randomised controlled trial of organisational change than a mindfulness programme [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%